Pengaruh Pemahaman Good Governance, Profesionalisme Terhadap Kinerja Auditor Dengan Time Pressure Sebagai Variabel Intervening - Nasution, Nadia; Hanum, Zulia (Owner : Riset dan Jurnal Akuntansi, 2024)
This research aims to test and analyze the influence of Understanding Good Governance, Professionalism on Auditor Performance with Time Pressure as an intervening variable. In this research, the author uses an associative approach, the data source used is primary data. The data collection technique used was by distributing questionnaires to 173 auditors who worked in a Medan City Public Accounting Office. The sample determination method was using the Slovin formula. The data analysis techniques used in this research are inner model analysis, inner model analysis and hypothesis testing using Partical Least Square (PLS) software version 4.1. The results of this research show that 1) Understanding Good Governance has no significant effect on Auditor Performance, 2) Understanding Good Governance has a significant effect on Time Pressure, 3) Professionalism has a significant effect on Auditor Performance, 4) Professionalism has a significant effect on Time Pressure, 5) Time Pressure has a significant effect on Auditor Performance, 6) Understanding Good Governance has a significant effect on Auditor Performance through Time Pressure, 7) Professionalism has a significant effect on Auditor Performance through Time Pressure.